Mono- and diiodo-1, 2, 3-triazoles and their mono nitro derivatives. Issue 23 (26th May 2016) - Chand, Deepak; He, Chunlin; Hooper, Joseph P.; Mitchell, Lauren A.; Parrish, Damon A.; Shreeve, Jean'ne M.
Abstract : An efficient synthetic route to mono and diiodo-1 H -1, 2, 3-triazoles. Abstract : 4-Iodo-1 H -1, 2, 3-triazole (2 ) and 4, 5-diiodo-1 H -1, 2, 3-triazole (3 ) were synthesized using an efficient and viable synthetic route. The N -alkylation of3 resulted in the formation of two tautomers. The N -alkyl-diiodo-triazoles were nitrated with 100% nitric acid to form monoiodo–mononitro-triazoles. The structures of 2-methyl-4, 5-diiodo-1, 2, 3-triazole (5 ), 1-ethyl-4, 5-diiodo-1, 2, 3-triazole (6 ), 1-methyl-4-nitro-5-iodo-1, 2, 3-triazole (8 ) and 1-ethyl-4-nitro-5-iodo-1, 2, 3-triazole (10 ) were confirmed by X-ray crystal analysis. All of the new triazoles were fully characterized via NMR, and infrared spectra, and elemental analyses as well as by their thermal and sensitivity properties. Decomposition products calculated using Cheetah 7 software show that these iodo–nitro triazoles liberate iodine.